P317 Exploring the lateralization of empathy for pain. Issue 9 (September 2017) - Taniguchi, Nami; Hironaga, Naruhito; Takei, Yuichi; Motoyama, Yoshimasa; Hayamizu, Mariko; Tobimatsu, Shozo
Abstract : Objectives: Empathy is crucial for communications in human social life. Recently, empathy for pain (EFP) has received attention in explorations of the intrinsic pain mechanism. Hemispheric lateralization is a characteristic of the human brain. The spatial profile of brain responses for EFP, including lateralization, has been explored in fMRI studies; however, the temporal profile remains largely unknown. Methods: We employed video stimuli consisting of pain and no-pain conditions and performed magnetoencephalographic recordings using stimuli of needle pain, cotton swab touch, and static for both left and right hands in 10 participants. We marked the anterior insula (AI) as a region of interest to determine the source waveforms for performing time–frequency analysis in both left and right hemispheres. We calculated induced power and inter-trial coherence using a wavelet transform and the mean alpha and beta frequency-range signals were extracted to compare laterality. Results: We found that a beta-band reduction in the left AI occurred within a specific time range, just around the time the needle penetrated the hand, regardless of which hand was penetrated. Discussion: We have recently demonstrated a spatiotemporal signature of cortical pain relief with special attention being paid to the posterior insula (Hayamizu et al., 2016), while anterior insula may response for EFP. Conculusion: Although further investigation is necessary to confirm hemispheric lateralization of EFP, one may assume that the left and right AI have different roles. Significance: This study is the first challenging to explore the temporal profiles of EFP in AI.